A mobile-based, single-session intervention to empower parents of adolescents hospitalised for non-suicidal self-injury: A mixed-methods randomised controlled trial - Juan He; Yidong Shen; Zengyu Chen; Yusheng Tian; Yanting Hou; Yamin Li; Jianjun Ou (Internet Interventions)
Background: Adolescents hospitalised for non-suicidal self-injury (NSSI) represent a particularly severe subset within psychiatric care. The NSSI imposes significant challenges on parents, including lack of knowledge, ineffective coping strategies, and negative emotions, exacerbated by stigma. Parental empowerment is crucial for supporting adolescent recovery; however, current interventions often neglect parents. Single-session interventions (SSIs) may offer an accessible and promising approach to address this gap. Methods: This mixed-methods study assessed the short-term effects of project CSH-P: a mobile-based, self-guided SSI aimed at empowering parents of adolescents hospitalised for NSSI. 88 participants were randomly assigned to CSH-P (n = 46) or control group (n = 42). Online assessments measuring knowledge, attitudes, and stigma were administered at baseline, immediately post-intervention, and one week later. Additionally, semi-structured individual interviews were conducted with participants who received CSH-P post-intervention. Results: Compared to the control group, participants who received CSH-P showed significant improvements in NSSI-related knowledge (Cohen’s d = .42, p = .027) and more positive attitudes toward their adolescents (Cohen’s d = - .31, p = .047). Qualitative findings confirmed these results, with parents reporting highly positive engagement and perceived empowerment across cognitive, emotional, and behavioural dimensions. Furthermore, parents provided constructive feedback for further enhancing the intervention’s impact. Conclusions: Project CSH-P demonstrates the potential to enhance parental empowerment in managing adolescent self-injurious behaviours. Its brevity, low cost, and ease of dissemination make it a promising strategy for widely applicable prevention and treatment efforts. Future research should explore the long-term sustainability of these improvements and assess the broader impact on parenting practices and adolescent treatment outcomes.